2012
DOI: 10.1177/2165143412450313
|View full text |Cite
|
Sign up to set email alerts
|

The Postsecondary Educational Plans of Rural Youth With Disabilities and Their Nondisabled Peers

Abstract: A national sample of students with disabilities and their nondisabled peers in rural high schools responded to a survey about their postsecondary plans and how they were preparing for them. The study included 3,318 11th-and 12th-grade students from 73 randomly selected schools. Findings indicate that 78.5% of students with disabilities and 90.7% of their nondisabled peers plan to continue their education after high school. Only 4.5% of students with disabilities were enrolled in a college preparatory program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Hitchings, Retish, and Horvath (2005) found that 77% of a sample of 110 high school sophomores with LDs expressed interest in attending college, but only four of them were enrolled in college preparatory classes. Moreover, Weiss, Hutchins, and Meece (2012) found that 79% of the students with LDs in their study reported wanting to continue their education after high school.…”
Section: The Consequences Of Rds and Mds In Adolescencementioning
confidence: 90%
“…Hitchings, Retish, and Horvath (2005) found that 77% of a sample of 110 high school sophomores with LDs expressed interest in attending college, but only four of them were enrolled in college preparatory classes. Moreover, Weiss, Hutchins, and Meece (2012) found that 79% of the students with LDs in their study reported wanting to continue their education after high school.…”
Section: The Consequences Of Rds and Mds In Adolescencementioning
confidence: 90%
“…Moreover, by the end of their junior year, only one student was still taking such courses. Weiss, Hutchins, and Meece (2012) collected data on 3,138 juniors and seniors from 73 randomly selected high schools in 34 states. The authors found that 79% of the students with disabilities reported wanting to continue their education after high school, but these students were statistically less likely than their peers to be enrolled in college preparatory classes and more likely to be in vocational programs.…”
mentioning
confidence: 99%